Negative electrode manufacturing method, negative electrode, and lithium secondary battery comprising same

CN122935822APending Publication Date: 2026-10-16LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580019904.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-01-03
Filing Date
2025-12-22
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,与未施加磁场的负极相比,通过磁场使负极活性材料取向的负极具有界面电阻较高的缺点

Benefits of technology

[0027] According to an exemplary embodiment of this disclosure, the interfacial adhesion between the negative electrode current collector and the negative electrode active layer is excellent, thereby minimizing the decrease in adhesion caused by the orientation of the negative electrode active material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122935822A_ABST
    Figure CN122935822A_ABST
Patent Text Reader

Abstract

The negative electrode according to the example embodiment of the present application includes a negative electrode current collector and a negative electrode active layer provided on at least one surface of the negative electrode current collector and including a carbon-based negative electrode active material, wherein the negative electrode active layer has a quantitative binder ratio (QBR) of 0.8 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a method for manufacturing a negative electrode, a negative electrode, and a lithium secondary battery containing the same.

[0002] This application claims the benefit of Korean Patent Application No. 10-2025-0000909, filed on January 3, 2025, the disclosure of which is incorporated herein by reference. Background Technology

[0003] In recent years, lithium secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium and large applications such as battery packs and energy storage systems (ESS) for hybrid and electric vehicles.

[0004] Generally, a lithium-ion secondary battery is a rechargeable power generation device comprising a stacked structure of a positive electrode, a separator, and a negative electrode. Graphite is widely used as the negative electrode active material. Graphite has a layered structure in which carbon atoms form a network structure spread out in planar layers, and many such layers are stacked on top of each other. During charging, lithium ions are inserted from the edge faces of the graphite layers (i.e., the surfaces of the stacked layers) and diffuse between the layers; during discharging, lithium ions are de-intercalated and released from the edge faces. Furthermore, since the resistivity of graphite in the in-plane direction (ab plane) is lower than that in the stacking direction (c axis), a circuitous electron conduction path is formed along the in-plane direction.

[0005] In this regard, to improve the charging performance of the negative electrode, a technique for magnetically oriented the graphite contained in the negative electrode has been proposed. Specifically, a negative electrode slurry is coated onto a negative electrode current collector, and a magnetic field is applied to the negative electrode slurry to orient the negative electrode active material. However, compared with a negative electrode without an applied magnetic field, a negative electrode with its active material oriented by a magnetic field has the disadvantage of higher interfacial resistance. Therefore, there is a need to develop a technique for improving the interfacial resistance of a negative electrode in which the active material is oriented by a magnetic field. Summary of the Invention

[0006] Technical issues

[0007] The technical idea behind this disclosure is to provide a magnetically oriented negative electrode with excellent interfacial adhesion between the current collector and the negative electrode active layer.

[0008] Technical solution

[0009] A negative electrode according to an exemplary embodiment of the present disclosure is provided. The negative electrode includes a negative electrode current collector; and a negative electrode active layer disposed on at least one surface of the negative electrode current collector and comprising a carbon-based negative electrode active material, wherein the QBR (quantitative binder ratio) of the negative electrode active layer is 0.8 or less, and the QBR is defined by the following Formula 1: [Formula 1] QBR = Bs / Bf In Equation 1, Bs represents the average adhesive content in the surface region of the negative electrode active layer within 15% of the total thickness of the negative electrode active layer, starting from the outermost surface of the negative electrode active layer, and Bf represents the average adhesive content in the bottom region of the negative electrode active layer within 15% of the total thickness of the negative electrode active layer, starting from the interface between the negative electrode active layer and the current collector.

[0010] In an exemplary embodiment, the QBR value of the negative electrode active layer calculated by Formula 1 is in the range of 0.1 to 0.75.

[0011] In an exemplary embodiment, when measured by X-ray diffraction (XRD) spectroscopy analysis, the orientation index (OI) of the negative electrode active layer, calculated by the following formula 2, is in the range of 1 to 15.

[0012] [Equation 2]

[0013] OI = I 004 / I 110

[0014] In Equation 2, I 004 This represents the peak area value corresponding to the [0,0,4] crystal plane when measured by XRD spectral analysis of the negative electrode active layer, and I 110 This represents the peak area value corresponding to the [1,1,0] crystal plane when measured by XRD spectral analysis of the negative electrode active layer.

[0015] In an exemplary embodiment, the carbon-based negative electrode active material comprises one or more mixtures selected from natural graphite, artificial graphite, floating graphite, pyrolytic carbon, carbon microspheres, mesophase carbon microspheres (MCMB) derived from tar / asphalt, and graphitized coke.

[0016] In an exemplary embodiment, the negative electrode active layer further comprises an adhesive, and the amount of the adhesive is 0.1 to 5 parts by weight relative to 100 parts by weight of the entire negative electrode active layer.

[0017] In an exemplary embodiment, the water contact angle of the current collector is less than 50°.

[0018] According to other embodiments of this disclosure, a method for manufacturing a negative electrode is provided. The method includes: modifying the surface of a negative electrode current collector; coating at least one surface of the negative electrode current collector with a negative electrode slurry comprising a carbon-based negative electrode active material; and applying a magnetic field to the coated negative electrode slurry, wherein modifying the surface of the negative electrode current collector includes a corona treatment process or a plasma treatment process.

[0019] In an exemplary embodiment, modifying the surface of the negative electrode current collector includes a process of corona treatment on the surface of the negative electrode current collector.

[0020] In an exemplary embodiment, the corona treatment is performed at an output power of 0.5 to 3.5 kW.

[0021] In an exemplary embodiment, the corona treatment is performed at a rate of 1 to 10 m / min.

[0022] The negative electrode manufacturing method according to an exemplary embodiment further includes: drying a negative electrode slurry to which a magnetic field has been applied; and calendering the dried negative electrode slurry to form a negative electrode active layer.

[0023] In an exemplary embodiment, during the step of applying the magnetic field, the strength of the magnetic field is in the range of 1,000 to 10,000 G.

[0024] In an exemplary embodiment, after modifying the surface of the negative electrode current collector, the water contact angle of the negative electrode current collector is less than 50°, preferably 1° to 40°.

[0025] In other embodiments of this disclosure, a lithium secondary battery is provided. The lithium secondary battery includes: a positive electrode; a negative electrode; a separator; and an electrolyte, wherein the negative electrode is the aforementioned negative electrode.

[0026] Beneficial effects

[0027] According to an exemplary embodiment of this disclosure, the interfacial adhesion between the negative electrode current collector and the negative electrode active layer is excellent, thereby minimizing the decrease in adhesion caused by the orientation of the negative electrode active material.

[0028] According to an exemplary embodiment of this disclosure, the orientation of the negative electrode active material improves the lithium-ion transport path in the negative electrode, thereby enabling a lithium secondary battery with improved fast charge and discharge characteristics. Attached Figure Description

[0029] Figure 1 This is a flowchart illustrating an exemplary embodiment of a negative electrode manufacturing method according to the present disclosure.

[0030] Figure 2 This is a graph showing the Bs and Bf values ​​of each negative electrode in the embodiments and comparative examples. Detailed Implementation

[0031] This disclosure will be described in more detail below to aid in understanding it.

[0032] The terms or words used in this specification and claims should not be construed as limited to their conventional or dictionary meanings, but should be interpreted based on the principle that the inventor can appropriately define the concepts of the terms in order to best describe his / her invention, and in accordance with the meanings and concepts consistent with the technical spirit of this disclosure.

[0033] The terminology used herein is for describing exemplary embodiments only and is not intended to limit the scope of this disclosure. Unless the context clearly indicates otherwise, singular expressions include plural expressions.

[0034] In this specification, terms such as “comprising,” “having,” or “including” are intended to indicate the presence of a feature, quantity, step, component, or combination thereof implemented, and should not be construed as excluding the possibility of the presence or addition of one or more other features, quantities, steps, components, or combinations thereof.

[0035] In this specification, when a portion of a layer, film, region, plate, etc., is described as being "on" another portion, this includes not only the case where it is "directly" "on" the other portion, but also the case where there are other portions between them. Conversely, when a portion is described as being "below" another portion, this includes not only the case where it is "directly" "below" the other portion, but also the case where there are other portions between them. Furthermore, in this application, "disposed on" can include both upper and lower portions.

[0036] In this specification, "bottom portion of the negative electrode active layer" refers to the area of ​​the negative electrode active layer near the negative electrode current collector, while "surface portion of the negative electrode active layer" refers to the area of ​​the negative electrode active layer near the outermost surface.

[0037] In this specification, "comprising as a major component" can mean comprising 50% by weight (or 50% by volume), 60% by weight (or 60% by volume), 70% by weight (or 70% by volume), 80% by weight (or 80% by volume), 90% by weight (or 90% by volume), or 95% by weight (or 95% by volume) of the defined component relative to the total weight (or total volume). For example, "comprising graphite as a major component as a negative electrode active material" can mean that the graphite content is 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more relative to the total weight of the negative electrode active material. In some cases, this may also mean that the entire negative electrode active material is composed of graphite (i.e., the graphite content is 100% by weight).

[0038] In this specification, "orienting the carbon-based anode active material" or "aligning the carbon-based anode active material" means that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) representing the two-dimensional planar structure of the carbon-based anode active material particles constituting the anode active material particles is arranged with a predetermined tilt relative to the surface of the anode current collector. This may differ from the arrangement of the carbon-based anode active material particles themselves in a specific direction within the anode active layer.

[0039] In this specification, "crystal plane of carbon-based anode active material" refers to the plane that forms the shape of the carbon-based anode active material crystal, and in this disclosure, it may refer to the crystal plane containing the carbon-based anode active material plane, or the crystal plane containing the a-axis / b-axis / ab-axis of the carbon-based anode active material crystal.

[0040] In this specification, "average particle size (D)" 50 ")" refers to the 50% point of the cumulative volume distribution based on particle size (D 50 The particle size. Average particle size (D) 50 It can be measured using methods commonly employed in the art. For example, it can be measured using a particle size analyzer or an analyzer that utilizes laser diffraction scattering particle size distribution measurement methods. 50 The particle size can be determined by calculating the cumulative volume distribution based on particle size and finding the point corresponding to 50% of the cumulative volume distribution based on particle size in the measuring device.

[0041] In this specification, the description of "A and / or B" means "A or B, or both".

[0042] Negative electrode manufacturing method

[0043] Figure 1 This is a flowchart illustrating an exemplary embodiment of a negative electrode manufacturing method according to the present disclosure.

[0044] Reference Figure 1 The negative electrode manufacturing method according to an exemplary embodiment may include modifying the surface of the negative electrode current collector (S11), coating with a negative electrode slurry (S12), and applying a magnetic field (S13). According to an exemplary embodiment, modifying the surface of the current collector (S11) may include a process of corona treatment on the surface of the negative electrode current collector or a process of plasma treatment on the surface of the negative electrode current collector.

[0045] When the surface of the negative electrode current collector is subjected to corona treatment or plasma treatment, the surface roughness of the negative electrode current collector increases. Surface roughness here refers to the degree of microscopic unevenness. This increase in surface roughness increases the contact area between the negative electrode current collector and the negative electrode active layer, thereby enhancing the interfacial adhesion between the negative electrode current collector and the negative electrode active layer.

[0046] Furthermore, when the surface of the negative electrode current collector is subjected to corona treatment or plasma treatment, hydrophilic functional groups can be introduced onto the surface of the negative electrode current collector. Since the negative electrode slurry is usually a solution in which the negative electrode active material and the binder are dispersed in an aqueous solvent, the bonding force between the surface-treated negative electrode current collector and the negative electrode slurry is higher than that between the untreated negative electrode current collector and the negative electrode slurry.

[0047] When the surface of the negative electrode current collector is subjected to corona treatment or plasma treatment, the wettability of the current collector to the negative electrode slurry is improved, allowing the magnetically oriented negative electrode active material to adhere more tightly to the surface of the current collector, thereby reducing the interfacial resistance between the negative electrode active material layer and the current collector.

[0048] In particular, compared to a negative electrode manufactured using an untreated current collector, a negative electrode manufactured using a surface-treated current collector according to this disclosure also exhibits a difference in the distribution of binder within the negative electrode active layer. The binder content in the bottom portion of the negative electrode active layer of the negative electrode manufactured according to this disclosure is higher than that of a negative electrode manufactured using an untreated current collector. The binder content in the surface portion of the negative electrode active layer of the negative electrode manufactured according to this disclosure is lower than that of a negative electrode manufactured using an untreated current collector. This is because the interaction between the hydrophilic functional groups on the surface-treated negative electrode current collector and the aqueous solvent in the negative electrode slurry makes it difficult for the binder in the negative electrode slurry to migrate to the surface of the negative electrode active layer during drying. Therefore, the negative electrode manufactured according to the exemplary embodiments of this disclosure has excellent interfacial adhesion between the current collector and the negative electrode active layer, thereby minimizing the decrease in adhesion caused by the orientation of the negative electrode active material.

[0049] Modifying the surface of the negative electrode current collector (S11) may include corona treatment or plasma treatment of the surface of the negative electrode current collector.

[0050] There are no particular limitations on the negative electrode current collector, as long as it has high conductivity but does not cause chemical changes in the battery. For example, copper, stainless steel, nickel, titanium, or sintered carbon can be used. In the case of copper or stainless steel, surface-treated products coated with carbon, nickel, titanium, or silver can also be used. Furthermore, considering the conductivity and total thickness of the manufactured negative electrode, the average thickness of the negative electrode current collector can be appropriately set in the range of 1 μm to 300 μm.

[0051] Corona treatment is a method that uses high-frequency current to ionize molecules in the air to generate high-temperature plasma. Corona treatment requires only simple electrodes and a high-frequency generator and is generally suitable for large-scale roll-to-roll production.

[0052] Plasma treatment is a method that uses high voltage to ionize a gas (such as argon, oxygen, or nitrogen) to create a plasma state, and then applies this plasma to the surface of a material to induce a chemical change. Plasma treatment requires a vacuum chamber or a high-voltage device, but it has the advantage of excellent surface modification uniformity.

[0053] The disadvantages of surface modification via plasma treatment are increased temperature of the negative electrode current collector and high processing cost. Since coating the negative electrode slurry onto the negative electrode current collector at elevated temperatures affects the physical properties of the negative electrode slurry, corona treatment is preferred as the surface modification method for the negative electrode current collector.

[0054] There are no particular restrictions on the specific methods and conditions for corona treatment, as long as it can increase the surface roughness of the negative electrode current collector or reduce the contact angle between the negative electrode current collector and water. Similarly, there are no particular restrictions on the specific methods and conditions for plasma treatment, as long as it can increase the surface roughness of the negative electrode current collector or reduce the contact angle between the negative electrode current collector and water.

[0055] In an exemplary embodiment, after modifying the surface of the negative electrode current collector (S11), the water contact angle of the negative electrode current collector can be less than 50°, preferably 1° to 40°, and more preferably 3° to 35°. When the water contact angle of the negative electrode current collector is within this range, the contact area between the negative electrode current collector and the negative electrode slurry increases, which can increase the binder content at the bottom of the negative electrode active layer.

[0056] In an exemplary embodiment, the output power during corona treatment can be in the range of 0.5 to 3.5 kW, preferably in the range of 1 to 3 kW, and more preferably in the range of 1.5 to 2.5 kW. When the output power is within this range, the adhesion of the negative current collector is excellent. When the output power is below this range, the effect of increasing adhesion is negligible. Conversely, when the output power exceeds this range, the uniformity of surface roughness may decrease.

[0057] In an exemplary embodiment, the corona treatment speed can be in the range of 1 to 10 m / min, preferably in the range of 2 to 8 m / min, and more preferably in the range of 3 to 6 m / min. When the corona treatment speed is within this range, the micro-unevenness generated by the corona treatment is uniformly formed, resulting in excellent adhesion of the negative electrode current collector.

[0058] Coating the negative electrode slurry (S12) is the step of coating at least one surface of a negative electrode current collector, wherein the negative electrode current collector is a surface-modified negative electrode current collector. The negative electrode slurry can be coated onto the surface of a moving negative electrode current collector. There are no particular limitations on the method of coating the negative electrode slurry, as long as it is a method commonly used in the art, but die coating is preferred. Die coating can be performed using a slit die equipped with a shim for controlling the discharge conditions of the negative electrode slurry. In this case, by adjusting the shape of the shim, the load and coating thickness of the negative electrode slurry applied to the negative electrode current collector can be easily controlled.

[0059] The negative electrode slurry can be prepared by adding and mixing a negative electrode active material and a binder to a solvent. The negative electrode slurry may further contain conductive materials and / or thickeners in addition to the negative electrode active material and the binder. The solvent can be an aqueous solvent, such as water. When the solvent is aqueous, the interaction between the aqueous solvent and the hydrophilic functional groups introduced onto the surface of the negative electrode current collector through surface treatment can inhibit the migration of the binder to the surface of the negative electrode active layer during drying. This minimizes the QBR value of the manufactured negative electrode and maximizes the effect of improving the interfacial adhesion between the negative electrode current collector and the negative electrode active layer.

[0060] The negative electrode active material may contain carbon-based negative electrode active material as the main component. The carbon-based negative electrode active material may contain graphite-based compounds. For example, the carbon-based negative electrode active material may contain one or more mixtures selected from natural graphite, artificial graphite, floating graphite, pyrolytic carbon, carbon microspheres, mesophase carbon microspheres (MCMB) derived from tar / pitch (bulk mesophase, liquid crystal pitch-based carbon fibers, etc.) and graphitized coke (raw coke, green coke, pitch coke, needle coke, petroleum coke, coal coke, etc.).

[0061] Based on the total weight of solids in the negative electrode slurry, the amount of the thickener may be 0.5 wt% to 3 wt%, 0.5 wt% to 2 wt%, 0.5 wt% to 1 wt%, 1 wt% to 3 wt%, 1 wt% to 2 wt%, 1.5 wt% to 3 wt%, 0.5 wt% to 1.9 wt%, or 1.1 wt% to 1.9 wt%.

[0062] Therefore, the negative electrode slurry can have a predetermined viscosity at room temperature (18°C to 27°C). Specifically, the viscosity of the negative electrode slurry at 25°C can be above 7,000 cps; specifically, 7,000 to 20,000 cps, 7,000 to 19,000 cps, 7,000 to 15,000 cps, 7,000 to 13,000 cps, 7,000 to 11,000 cps, 11,000 to 19,000 cps, 13,000 to 18,000 cps, 15,000 to 18,000 cps, 7,000 to 9,000 cps, 8,000 to 10,000 cps, 9,000 to 11,000 cps, 7,000 to 8,500 cps, or 7,100 to 7,900 cps.

[0063] The step of applying the magnetic field (S13) can be a process of controlling the crystallization characteristics of the negative electrode active material contained in the negative electrode slurry to reduce the disorder of the carbon-based negative electrode active material contained in the negative electrode slurry. By applying a magnetic field to the negative electrode slurry coated on the negative electrode current collector in the step of applying the magnetic field (S13), the ab-axis crystal planes of the carbon-based negative electrode active material contained in the negative electrode slurry can be aligned to form a large tilt angle relative to the negative electrode current collector.

[0064] In an exemplary embodiment, the magnetic field can be applied by magnetic portions disposed on the upper and lower parts of a negative electrode current collector coated with a negative electrode paste. The polarities of the upper and lower magnetic portions can be different or the same.

[0065] The orientation index (OI) of the carbon-based anode active material contained in the anode slurry can be controlled by the strength and duration of the applied magnetic field. Therefore, the step of applying the magnetic field can be carried out under predetermined magnetic field strength and duration conditions.

[0066] In the step of applying the magnetic field (S13), a magnetic field of less than 10,000 G (Gauss) can be applied; specifically, 1,000 G to 10,000 G, 3,000 G to 9,000 G, 3,000 G to 8,500 G, 3,500 G to 8,500 G, 4,000 G to 8,200 G, 3,600 G to 4,500 G, 4,500 G to 6,500 G, 5,000 G to 7,000 G, 6,000 G to 8,500 G, 7,000 G to 8,500 G, 6,000 G to 6,500 G, or 4,000 G to 5,000 G.

[0067] The step of applying the magnetic field (S13) can be performed for 1 to 30 seconds, specifically 1 to 20 seconds, 1 to 15 seconds, 1 to 10 seconds, 5 to 20 seconds, 10 to 20 seconds, 11 to 19 seconds, 14 to 18 seconds, 4 to 9 seconds, or 6 to 11 seconds, but is not limited thereto.

[0068] As an example, in the step of applying the magnetic field (S13), a magnetic field of 4,700±50G can be applied to the negative electrode slurry for 3 to 8 seconds.

[0069] As another example, in the step of applying the magnetic field (S13), a magnetic field of 4,700±50G can be applied to the negative electrode slurry for 12 to 17 seconds.

[0070] The step of applying the magnetic field (S13) can be performed by introducing magnet portions at the top and bottom of the coated negative electrode slurry, wherein the size of the magnet portions is adjusted to be larger than the size of the negative electrode slurry coating portion. For example, the length ratio of the magnet portions relative to the width direction length of the negative electrode slurry coating portion can be 105% to 200%, specifically 110% to 180%, 110% to 160%, 110% to 140%, 110% to 130%, 130% to 150%, or 105% to 120%. In this case, since the magnetic field applied to the negative electrode slurry is uniformly applied to the entire surface of the negative electrode slurry coating portion, the orientation index (OI) of the carbon-based negative electrode active material can be uniformly achieved.

[0071] The negative electrode manufacturing method according to this disclosure may further include a step of drying a negative electrode slurry to which a magnetic field has been applied (S14) and a step of calendering the dried negative electrode slurry to form a negative electrode active layer (S15). The drying step (S14) and the calendering step (S15) are processes for drying and calendering the magnetically oriented negative electrode slurry to firmly fix the oriented carbon-based negative electrode active material. There are no particular limitations on the drying step (S14) and the calendering step (S15), as long as they are performed in a manner that maintains the orientation index (OI) of the carbon-based negative electrode active material contained in the negative electrode active layer.

[0072] The drying step (S14) can be performed by applying heat energy using a hot air dryer, a vacuum oven, or the like to dry the negative electrode slurry. However, the drying method is not limited to this.

[0073] The calendering step (S15) is a step that increases the density of the negative electrode active layer by applying pressure to the dried negative electrode slurry using a roller press or the like. In some embodiments, the calendering step (S15) can be performed without increasing the orientation index (OI) of the carbon-based negative electrode active material in the dried negative electrode slurry.

[0074] The calendering step (S15) can be carried out at a temperature close to room temperature, more specifically, at a temperature of 20°C to 35°C, 20°C to 30°C, or 20°C to 25°C.

[0075] The calendering step (S15) can be carried out at a pressure of 50 MPa to 200 MPa, specifically 50 MPa to 150 MPa, 50 MPa to 100 MPa, 100 MPa to 200 MPa, 150 MPa to 200 MPa or 80 MPa to 140 MPa.

[0076] By performing the calendering step (S15) under the above temperature and / or pressure conditions, the change in the orientation index of the carbon-based anode active material contained in the anode active layer can be minimized, while the energy density of the anode can be increased.

[0077] When measured by X-ray diffraction (XRD) spectral analysis, the orientation index (OI) of the negative electrode active layer of the negative electrode manufactured according to the exemplary embodiment, calculated by the following formula 2, can be in the range of 1 to 15.

[0078] [Equation 2]

[0079] OI = I 004 / I 110

[0080] In Equation 2, I 004 This represents the peak area value corresponding to the [0,0,4] crystal plane when measured by XRD spectral analysis of the negative electrode active layer, and I 110 This represents the peak area value corresponding to the [1,1,0] crystal plane when measured by XRD spectral analysis of the negative electrode active layer.

[0081] Here, the orientation index (OI) is based on the post-calendering state. The post-calendering orientation index (OI) can be in the range of 1 to 15, specifically in the range of 1 to 12, and more specifically in the range of 1 to 10.

[0082] In an exemplary embodiment, the pre-calendering orientation index (OI) of the negative electrode can be in the range of 0.1 to 8, specifically in the range of 0.1 to 6, and more specifically in the range of 0.1 to 5.

[0083] The negative electrode manufactured according to the exemplary embodiments of this disclosure satisfies the orientation index within the aforementioned range, thereby exhibiting excellent fast-charging performance. Furthermore, the excellent adhesion between the negative electrode current collector and the negative electrode active layer ensures excellent long-term capacity characteristics, enabling the realization of lithium-ion secondary batteries with high energy density.

[0084] negative electrode

[0085] An exemplary embodiment of the present disclosure provides a negative electrode comprising a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector and comprising a carbon-based negative electrode active material. The QBR (quantitative binder ratio) of the negative electrode active layer is 0.8 or less, and the QBR can be defined by the following formula 1: [Formula 1] QBR = Bs / Bf In Equation 1, Bs represents the average adhesive content in the surface region of the negative electrode active layer within 15% of the total thickness of the negative electrode active layer, starting from the outermost surface of the negative electrode active layer, and Bf represents the average adhesive content in the bottom region of the negative electrode active layer within 15% of the total thickness of the negative electrode active layer, starting from the interface between the negative electrode active layer and the current collector.

[0086] Bs and Bf can be calculated using the following method. The negative electrode sample is immersed in a diluted OsO4 solution (approximately 0.1% concentration) for about 30 minutes to stain the adhesive components with OsO4. Subsequently, the OsO4-stained osmium components on the adhesive are detected using an energy-dispersive X-ray spectroscopy (EDS) analyzer attached to a scanning electron microscope (SEM) (SU8020, Hitachi). EDS mapping images showing the detected osmium spots are extracted. The extracted EDS mapping images are image-processed to calculate the area of ​​the stained adhesive and the area of ​​the unstained portion, respectively. The region from the outermost surface of the negative electrode active layer to 15% of the total thickness of the negative electrode active layer is defined as the "surface portion of the negative electrode active layer," and the region from the interface between the negative electrode active layer and the current collector to 15% of the total thickness of the negative electrode active layer is defined as the "bottom portion of the negative electrode active layer." In the surface portion of the negative electrode active layer, the ratio (Os / C) of the stained adhesive area (Os) to the unstained area (C) is calculated, and the average of this ratio (Os / C) for multiple samples is calculated as Bs. Similarly, in the bottom portion of the negative electrode active layer, the ratio (Os / C) is calculated, and the average of multiple samples is calculated as Bf.

[0087] The negative electrode according to the exemplary embodiment of this disclosure can be manufactured by the method described above. That is, it is manufactured by coating a negative electrode slurry onto a negative electrode current collector treated with corona or plasma and applying a magnetic field to the coated negative electrode slurry. Therefore, the negative electrode according to this disclosure satisfies that the QBR calculated by Formula 1 for the binder content Bf of the bottom portion and the binder content Bs of the surface portion of the negative electrode active layer is 0.8 or less, preferably 0.1 to 0.75, and more preferably 0.3 to 0.7. When the QBR meets this range, excellent adhesion between the negative electrode current collector and the negative electrode active layer is achieved.

[0088] The negative electrode active material may contain carbon-based negative electrode active material as its main component. The carbon-based negative electrode active material refers to a material with carbon atoms as its main component, and this carbon-based negative electrode active material may contain graphite-based compounds. For example, the carbon-based negative electrode active material may contain one or more mixtures selected from natural graphite, artificial graphite, floating graphite, pyrolytic carbon, carbon microspheres, mesophase carbon microspheres (MCMB) derived from tar / pitch (bulk mesophase, liquid crystal pitch-based carbon fibers, etc.), and graphitized coke (raw coke, green coke, pitch coke, needle coke, petroleum coke, coal coke, etc.).

[0089] The carbon-based negative electrode active material can have shapes such as plates, sheets, scales, or needles, or it can be spherical particles. Here, spherical particle shape can refer to particles without sharp edges or corners. Such particles can have spherical or ellipsoidal shapes when performing cross-sectional structural analysis or as two-dimensional particle projections, and in some cases, they can be amorphous.

[0090] In one embodiment, the carbon-based negative electrode active material can be graphite with a spherical particle morphology. In this case, the spherical particles can be processed into a spherical shape / morphology during manufacturing, or they can be spherical secondary graphite aggregates assembled from multiple flake-like primary graphite particles. By controlling the morphology of the carbon-based negative electrode active material as described above, this disclosure can improve the conductivity of the negative electrode active layer and maximize the contact area with the negative electrode current collector, thereby enhancing the adhesion between the negative electrode active layer and the negative electrode current collector.

[0091] In another embodiment, the carbon-based anode active material may have a flake or plate-like particle morphology. In this case, the carbon-based anode active material can shorten the lithium-ion transport path within the anode active layer, resulting in excellent fast-charging performance.

[0092] In one embodiment, the carbon-based negative electrode active material can be in the form of an aggregate formed by the assembly of multiple particles. In this case, a graphite aggregate can be formed by the assembly of 2 to 100, preferably 3 to 20, graphite particles.

[0093] For high densification of the negative electrode active layer, the average particle size of the carbon-based negative electrode active material may be within a predetermined range. Specifically, the average particle size D of the carbon-based negative electrode active material 50 ) may be 0.5 μm to 20 μm; specifically 0.5 μm to 15 μm, 0.5 μm to 10 μm, 5 μm to 20 μm, 10 μm to 20 μm, 12 μm to 18 μm, 2 μm to 7 μm, 0.5 μm to 5 μm, or 1 μm to 3 μm. To suppress particle expansion caused by lithium ion intercalation, it is advantageous to reduce the average particle size of the carbon-based negative electrode active material to maximize the disorder degree of each particle in the expansion direction. However, when the particle size of the carbon-based negative electrode active material is less than 0.5 μm, the number of particles per unit volume increases, which may require a large amount of binder. On the other hand, when the maximum particle size exceeds 20 μm, the expansion becomes severe, and as charge and discharge cycles are repeated, the binding force between particles and between particles and the current collector decreases, resulting in reduced cycle performance.

[0094] The negative electrode active material may further include a silicon-based negative electrode active material.

[0095] The silicon-based negative electrode active material is a material containing silicon (Si) as a main component, and is capable of increasing the charge-discharge capacity and volumetric energy density of the negative electrode. Examples of the silicon-based negative electrode active material include silicon (Si), silicon carbide (SiC), and silicon oxide (SiO X , where 0<x<2), and these may be included in the negative electrode active layer alone or in combination.

[0096] The silicon-based negative electrode active material may be doped with Li, Mg, Al, Ca and / or Ti or form an alloy therewith. In addition, when the silicon-based negative electrode active material contains oxygen (O), for the purpose of suppressing volume expansion during charging and improving the conductivity of the negative electrode active material, the surface thereof may be subjected to surface treatment with a carbon coating or the like.

[0097] Based on the total weight of the negative electrode active layer, the amount of silicon-based negative electrode active material present can be from 0.1 wt% to 30 wt%. Specifically, based on the total weight of the negative electrode active layer, the amount of silicon-based negative electrode active material present can be from 0.1 wt% to 25 wt%, 20 wt% to 30 wt%, 10 wt% to 30 wt%, 0.5 wt% to 20 wt%, 1 wt% to 9 wt%, 5 wt% to 15 wt%, 3 wt% to 7 wt%, 11 wt% to 19 wt%, 13 wt% to 17 wt%, 15 wt% to 20 wt%, 3 wt% to 13 wt%, or 1 wt% to 15 wt%. This disclosure, by adjusting the content ratio of the silicon-based negative electrode active material within the above ranges, can reduce lithium consumption and irreversible capacity loss during the initial charge-discharge period of the secondary battery, while improving the gravimetric charging capacity. Furthermore, by minimizing the volume change of the negative electrode active layer during the charge-discharge period of the secondary battery, the structural stability of the negative electrode active layer can be improved, thereby enhancing the cycle life of the secondary battery.

[0098] The conductive material may include one or more of the following: carbon black, such as acetylene black, danca black, kejjung black, Super-P, furnace black, lamp black and thermal cracking carbon black; graphene; carbon nanotubes; and carbon fibers; but not limited thereto.

[0099] As an example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc., as conductive materials, either alone or in combination.

[0100] The content of the conductive material relative to 100 parts by weight of the entire negative electrode active layer can be from 0.1 to 10 parts by weight. Specifically, the amount of the conductive material relative to 100 parts by weight of the entire negative electrode active layer can be from 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 2 to 6 parts by weight, or 0.5 to 2 parts by weight. By controlling the content of the conductive material within the above range, this disclosure can prevent an increase in negative electrode resistance due to a low content of conductive material, which would otherwise reduce the charging capacity. Furthermore, this disclosure can prevent a decrease in charging capacity due to a decrease in the content of negative electrode active material caused by an excess of conductive material, or an increase in resistance due to an increase in the loading of the negative electrode active layer.

[0101] Furthermore, the adhesive is a component that facilitates the bonding of the negative electrode active material with the conductive material and with the current collector, and can be used appropriately without reducing the electrical performance of the negative electrode. For example, the adhesive may contain one or more of the following: vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber.

[0102] The content of the adhesive relative to 100 parts by weight of the entire negative electrode active layer can be 0.1 to 10 parts by weight, preferably 0.1 to 5 parts by weight. Specifically, the amount of adhesive present relative to 100 parts by weight of the entire negative electrode active layer can be 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight. By controlling the content of adhesive in the negative electrode active layer within the above range, this disclosure can prevent a decrease in the adhesion of the active layer due to a low adhesive content or a decrease in the negative electrode electrical performance due to an excessive amount of adhesive.

[0103] The average thickness of the negative electrode active layer can be in the range of 100 μm to 400 μm; for example, 100 μm to 350 μm, 100 μm to 300 μm, 100 μm to 250 μm, 100 μm to 200 μm, 150 μm to 400 μm, 200 μm to 400 μm, 150 μm to 300 μm, 150 μm to 250 μm or 150 μm to 220 μm.

[0104] According to exemplary embodiments of the present disclosure, the adhesion between the negative electrode current collector and the negative electrode active layer can be 20 gf / 20 mm or more, specifically in the range of 20 to 50 gf / 20 mm, 23 to 40 gf / 20 mm, or 25 to 35 gf / 20 mm. Therefore, the negative electrode of the present disclosure exhibits excellent long-term capacity and cycle performance.

[0105] The negative electrode according to the exemplary embodiments of this disclosure, by having the above configuration, shortens the lithium-ion transport path within the negative electrode active layer, significantly reduces the diffusion resistance of lithium ions, and achieves excellent fast-charging performance. Furthermore, the excellent adhesion between the negative electrode current collector and the negative electrode active layer minimizes the reduction in adhesion caused by the orientation of the negative electrode active material relative to the negative electrode current collector at a predetermined angle, resulting in excellent durability and superior long-term capacity and cycle performance.

[0106] Lithium secondary batteries

[0107] Next, a lithium secondary battery according to this disclosure will be described.

[0108] A lithium secondary battery according to an exemplary embodiment of this disclosure includes a positive electrode; a negative electrode; a separator; and an electrolyte, wherein the negative electrode may be the aforementioned negative electrode. Since the negative electrode has already been described in detail above, a repetition of that description will be omitted.

[0109] The lithium secondary battery disclosed herein can be manufactured according to conventional methods known in the art. For example, it can be manufactured by placing a separator between the positive and negative electrodes and injecting an electrolyte.

[0110] Compared to a negative electrode using an untreated negative electrode current collector, a negative electrode manufactured according to this disclosure, even with the same composition of the negative electrode active layer, has a higher binder content at the bottom portion of the negative electrode active layer and a lower binder content at the surface portion of the negative electrode active layer.

[0111] The positive electrode may include a positive electrode current collector and a positive electrode active layer formed on the positive electrode current collector and containing positive electrode active material.

[0112] Regarding the positive electrode, there are no particular restrictions on the positive electrode current collector, as long as it is conductive but does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, or sintered carbon can be used, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, or silver. Furthermore, the thickness of the positive electrode current collector can typically be 3 to 500 μm, and micro-protrusions can be formed on the surface of the current collector to increase the adhesion of the positive electrode active material. For example, it can be used in various forms, such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.

[0113] There are no particular limitations on the positive electrode active material, and any compound known in the art capable of reversibly inserting and deintercalating lithium can be used without restriction. Specifically, the positive electrode active material may comprise: layered compounds, such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or compounds substituted with one or more transition metals; lithium manganese oxide, such as Li... 1+x Mn 2-x O4 (where x = 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, LiV3O4, V2O5 and Cu2V2O; and LiNi 1-x M xNi-site type lithium nickel oxide represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); by chemical formula LiMn 2-x M x Lithium manganese composite oxides represented by O2 (where M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); and LiNi x Mn 2-x Lithium manganese composite oxide with spinel structure represented by O4; LiMn2O4 in which a portion of Li is replaced by alkaline earth metal ions; disulfide compounds; lithium iron phosphate represented by LiFePO4; and Fe2(MoO4)3; but not limited thereto.

[0114] In addition to the aforementioned positive electrode active material, the positive electrode active material layer may also include a positive electrode conductive material and a positive electrode binder.

[0115] The positive electrode conductive material is used to impart conductivity to the electrode. Carbon black, graphite, carbon fiber, carbon nanotubes, metal powder, conductive metal oxides, organic conductive materials, etc., can be used. Commercially available conductive materials include acetylene black series (products of Chevron Chemical Company or Gulf Oil Company), Ketjen Black EC series (product of Armak), Vulcan XC-72 (product of Cabot), and Super P (product of MMM). Among these, carbon nanotubes, carbon nanofibers, and carbon black are preferred as the conductive materials in this disclosure, with carbon nanotubes being the most preferred.

[0116] In the positive electrode active material layer, the amount of the positive electrode conductive material may be from 0.1 wt% to 30 wt%, specifically from 0.1 wt% to 10 wt%, more specifically from 0.5 wt% to 5 wt%.

[0117] Any commonly used adhesive polymer can be used as the positive electrode adhesive without restriction. For example, various types of adhesive polymers can be used, such as polyvinylidene fluoride-hexafluoropropylene (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC).

[0118] In the positive electrode active material layer, the amount of the positive electrode binder can be from 0.1% by weight to 30% by weight, specifically from 0.1% by weight to 10% by weight, and more specifically from 0.5% by weight to 5% by weight.

[0119] The separator can be any porous substrate commonly used as a separator in lithium secondary batteries. For example, polyolefin-based porous membranes or nonwoven fabrics can be used, but the separator is not particularly limited to these. In particular, the separator is preferably a separator that has low resistance to ion transport in the electrolyte and excellent electrolyte wettability.

[0120] Examples of the polyolefin-based porous membranes include membranes formed from polyolefin polymers such as polyethylene (including high-density polyethylene, linear low-density polyethylene, low-density polyethylene, and ultra-high molecular weight polyethylene), polypropylene, polybutene, and polypentene, which are used individually or as mixtures thereof.

[0121] Besides polyolefin-based nonwoven fabrics, the nonwoven fabric can also be a nonwoven fabric formed from polymers used individually or as mixtures thereof, such as polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, and polyethylene naphthalate. The structure of the nonwoven fabric can be a spunbond nonwoven fabric or a meltblown nonwoven fabric composed of long fibers.

[0122] There is no particular limitation on the thickness of the porous substrate, but it can be from 5 to 50 μm. There is also no particular limitation on the pore size and porosity present in the porous substrate, but they can be from 0.01 to 50 μm and from 10% to 95%, respectively.

[0123] On the other hand, in order to improve the mechanical strength of the membrane made of porous substrate and suppress short circuits between the positive and negative electrodes, at least one surface of the porous substrate may further include a porous coating containing inorganic particles and a binder polymer.

[0124] On the other hand, in lithium secondary batteries, the electrolyte may contain organic solvents and lithium salts commonly used as electrolytes, and there are no particular limitations.

[0125] The organic solvent can be used without particular restriction, as long as it can serve as a medium through which ions participating in the battery electrochemical reaction can move. Specifically, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; and carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC) can be used.

[0126] Carbonate-based solvents are preferred. More preferably, a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant, which can enhance the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate).

[0127] The lithium salt can be used without particular restriction, as long as it is a compound capable of providing lithium ions for use in lithium secondary batteries. Specifically, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2 can be used. The lithium salt is preferably contained in the electrolyte at a concentration of about 0.6 mol% to 2 mol%.

[0128] To improve cycle life characteristics, suppress battery capacity reduction, and enhance battery discharge capacity, the electrolyte, in addition to the aforementioned electrolyte components, may also contain one or more additives, such as pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, hexamethylphosphoryltriamine, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolides, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride. In this case, based on the total weight of the electrolyte, the content of the additives may be from 0.1% by weight to 5% by weight.

[0129] The lithium secondary battery of this disclosure can be manufactured by arranging a separator between the positive and negative electrodes to form an electrode assembly, placing the electrode assembly in a cylindrical or square battery case, and then injecting the electrolyte. Alternatively, the electrode assemblies can be stacked, then immersed in the electrolyte, and the resulting product can be placed in a battery case and sealed.

[0130] When manufacturing the lithium secondary battery of this disclosure, the electrode assembly can be dried to remove one or more organic solvents selected from the group consisting of N-methyl-2-pyrrolidone (NMP), acetone, ethanol, propylene carbonate, ethyl methyl carbonate, ethylene carbonate, and dimethyl carbonate used in the manufacture of the positive electrode. If an electrolyte with the same composition as the organic solvent used in the manufacture of the positive electrode is used as the electrolyte, the step of drying the electrode assembly can be omitted.

[0131] Unlike the lithium secondary battery described above, another embodiment of the lithium secondary battery according to this disclosure can be an all-solid-state battery.

[0132] The battery casing can be of any type commonly used in the art, and its external shape is not limited depending on the intended use of the battery. For example, it can be cylindrical, square, pouch-shaped, or coin-shaped, similar to a can.

[0133] Because the lithium secondary battery according to this disclosure stably exhibits excellent resistance characteristics, discharge capacity, output characteristics and capacity retention, it can be used in portable devices such as mobile phones, laptops and digital cameras, energy storage systems (ESS), and electric vehicles such as hybrid electric vehicles (HEVs).

[0134] The present disclosure will be described in more detail below with reference to the following embodiments. However, the following embodiments are provided merely as examples of the present disclosure and do not limit the scope of the invention.

[0135] Example

[0136] Prepare copper foil as the negative electrode current collector. Apply corona treatment to both surfaces of the copper foil. During the corona treatment, the speed is set to 3 m / min and the output power is set to 1.5 kW.

[0137] The average particle size D, which is used as the negative electrode active material 50 A negative electrode slurry with a solids content of 50% by weight was prepared by adding 1 to 10 μm flake-like artificial graphite, styrene-butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener to water as a solvent. The solids content composition was set as follows: per 100 parts by weight of total solids, 96.5 parts by weight of negative electrode active material, 2.5 parts by weight of binder, and 1.0 part by weight of thickener.

[0138] The negative electrode paste is coated onto a corona-treated copper foil. A permanent magnet, with a length ratio of 110% to 120% relative to the width of the coated negative electrode paste, is arranged above the coated negative electrode paste and below the negative electrode current collector, and a magnetic field of 4,700 ± 20 G is applied for 8 seconds. The negative electrode paste with the applied magnetic field is dried with hot air and then rolled to manufacture the negative electrode. The average thickness of the negative electrode active layer of the manufactured negative electrode is 120 ± 5 μm.

[0139] Comparative example

[0140] The negative electrode is manufactured in the same manner as in Example 1, except that the negative current collector is not corona treated.

[0141] Experimental Example 1: QBR

[0142] Five negative electrode samples each from the Examples and Comparative Examples were prepared. The cross-sections of the prepared negative electrode samples were ion-milled. The ion-milled negative electrode samples were immersed in a diluted OsO4 solution (approximately 0.1% concentration) for approximately 30 minutes to stain the binder component with OsO4. Subsequently, the OsO4-stained osmium component on the binder was detected using an EDS (Energy Dispersive X-ray Spectrometry) analyzer attached to a scanning electron microscope (SEM) (SU8020, Hitachi). EDS mapping images showing the detected osmium spots were extracted. The extracted EDS mapping images were image-processed to calculate the stained area and the unstained area of ​​the binder, respectively. The region from the outermost surface of the negative electrode active layer to 15% of the total thickness of the negative electrode active layer was defined as the "surface portion of the negative electrode active layer," and the region from the interface between the negative electrode active layer and the current collector to 15% of the total thickness of the negative electrode active layer was defined as the "bottom portion of the negative electrode active layer." In the surface portion of the negative electrode active layer as defined herein, the ratio (Os / C) of the stained adhesive area (Os) to the unstained area (C) is calculated, and the average of this ratio (Os / C) for five samples is calculated as Bs. Similarly, in the bottom portion of the negative electrode active layer, this ratio (Os / C) is calculated, and the average of five samples is calculated as Bf. The average Bs and average Bf values ​​of each negative electrode sample of the Examples and Comparative Examples are shown below. Figure 2 middle.

[0143] Furthermore, the QBR value was calculated by substituting the Bs and Bf values ​​into Equation 1 below, and the results are shown in Table 1.

[0144] [Formula 1]

[0145] QBR = Bs / Bf

[0146] Experimental Example 2: Adhesion Force Evaluation

[0147] The negative electrodes manufactured in the examples and comparative examples were each cut into 25 mm × 70 mm (width × length) dimensions to prepare samples. The prepared samples were attached to a glass plate using double-sided tape, with the current collector facing the glass plate. The samples fixed to the glass plate were then placed in a tensile testing machine, and the negative electrode active layer of each negative electrode was peeled off at 25°C and a speed of 100 mm / min at a 90° angle relative to the negative electrode current collector. The peel force measured in real time is shown in Table 1.

[0148] Experimental Example 3: Cyclic Life Performance Evaluation

[0149] D, as the positive electrode active material 50 5 μm LiNi 0.7 Co 0.1 Mn 0.1 Al0.1 O2, carbon black as a conductive material, and polyvinylidene fluoride as a binder are added to N-methylpyrrolidone (NMP) as a solvent in a weight ratio of 94:3:3 and mixed to prepare a positive electrode slurry. The positive electrode slurry is coated onto aluminum foil, then dried and calendered to manufacture the positive electrode.

[0150] A separator made of 18 μm polypropylene is inserted between the positive electrode and each negative electrode from the examples and comparative examples, inserted into the casing, and then an electrolyte composition is injected to assemble the lithium secondary battery.

[0151] Each lithium-ion secondary battery was activated by charging to 3.6 V at 0.3 C under CC-CV conditions at 23°C. They were then aged at 60°C for 36 hours, followed by aging at 23°C for 48 hours. Subsequently, a degassing process was performed to remove gases generated inside the secondary batteries, followed by full charging and full discharging.

[0152] Subsequently, one cycle was defined as charging each lithium secondary battery to 4.2 V at 1.0 C under CC-CV conditions at 23°C, and then discharging it to 2.5 V at 1.0 C under CC conditions. Here, the lithium secondary batteries manufactured in the Examples and Comparative Examples underwent their first charge-discharge cycle. During this time, the charge-discharge capacity was measured during the charge-discharge cycle to confirm the charge-discharge capacity of the first cycle. Subsequently, 299 more charge-discharge cycles were performed, for a total of 300 cycles. The charge-discharge capacity of the 300th cycle was confirmed during the final cycle. The capacity retention rate of the 300th cycle was calculated based on the measured charge-discharge capacity of the first cycle. The results are shown in Table 1.

[0153] [Table 1]

[0154] Referring to Table 1, the average Bf value of the negative electrode according to the embodiment is greater than the average Bf value of the negative electrode according to the comparative example, and the average Bs value of the negative electrode according to the embodiment is less than the average Bs value of the negative electrode according to the comparative example. That is, the binder content at the bottom portion of the negative electrode active layer of the negative electrode according to the embodiment is higher than the binder content at the bottom portion of the negative electrode active layer of the negative electrode according to the comparative example, and the binder content at the surface portion of the negative electrode active layer of the negative electrode according to the embodiment is lower than the binder content at the surface portion of the negative electrode active layer of the negative electrode according to the comparative example. Therefore, the adhesion strength of the negative electrode according to the embodiment is higher than that of the negative electrode according to the comparative example. Furthermore, compared to the negative electrode according to the comparative example, the negative electrode according to the embodiment exhibits superior long-term cycling performance in secondary batteries.

[0155] The present disclosure has been described in more detail with reference to the accompanying drawings and embodiments. However, it should be understood that the configurations described in the drawings or embodiments herein are merely one implementation of the present disclosure and do not represent the full technical scope of the present disclosure. Therefore, various equivalents and modifications may exist at the time of filing this application.

Claims

1. A negative electrode, said negative electrode comprising: Negative current collector; and A negative electrode active layer comprising a carbon-based negative electrode active material is disposed on at least one surface of the negative electrode current collector, wherein... The QBR (quantitative binder ratio) of the negative electrode active layer is 0.8 or less, and the QBR is defined by the following formula 1: [Formula 1] QBR = Bs / Bf In Equation 1, Bs represents the average adhesive content in the surface region of the negative electrode active layer within 15% of the total thickness of the negative electrode active layer, starting from the outermost surface of the negative electrode active layer, and Bf represents the average adhesive content in the bottom region of the negative electrode active layer within 15% of the total thickness of the negative electrode active layer, starting from the interface between the negative electrode active layer and the current collector.

2. The negative electrode according to claim 1, wherein The QBR value of the negative electrode active layer, calculated by Equation 1, is in the range of 0.1 to 0.

75.

3. The negative electrode according to claim 1, wherein When measured by X-ray diffraction (XRD) spectroscopy analysis, the orientation index (OI) of the negative electrode active layer, calculated by the following formula 2, is in the range of 1 to 15: [Equation 2] OI =I 004 / I 110 In Equation 2, I 004 This represents the peak area value corresponding to the [0,0,4] crystal plane when measured by XRD spectral analysis of the negative electrode active layer, and I 110 This represents the peak area value corresponding to the [1,1,0] crystal plane when measured by XRD spectral analysis of the negative electrode active layer.

4. The negative electrode according to claim 1, wherein The carbon-based negative electrode active material comprises one or more of the following: natural graphite, artificial graphite, floating graphite, pyrolytic carbon, carbon microspheres, mesophase carbon microspheres (MCMB) derived from tar / asphalt, and graphitized coke.

5. The negative electrode according to claim 1, wherein The negative electrode active layer also includes an adhesive, and The amount of the adhesive is 0.1 to 5 parts by weight relative to 100 parts by weight of the entire negative electrode active layer.

6. The negative electrode according to claim 1, wherein The water contact angle of the current collector is less than 50°.

7. A method for manufacturing a negative electrode, the method comprising: The surface of the negative electrode current collector is modified; A negative electrode slurry containing a carbon-based negative electrode active material is coated on at least one surface of the negative electrode current collector; and A magnetic field is applied to the coated negative electrode slurry, wherein Modifying the surface of the negative electrode current collector includes either corona treatment of the surface of the negative electrode current collector or plasma treatment of the surface of the negative electrode current collector.

8. The negative electrode manufacturing method according to claim 7, wherein Modifying the surface of the negative electrode current collector includes a process of corona treatment on the surface of the negative electrode current collector.

9. The negative electrode manufacturing method according to claim 7, wherein... The corona treatment is performed at an output power of 0.5 to 3.5 kW.

10. The negative electrode manufacturing method according to claim 7, wherein The corona treatment is performed at a rate of 1 to 10 m / min.

11. The negative electrode manufacturing method according to claim 7, the method further comprising: The negative electrode slurry, to which a magnetic field has been applied, is dried; and The dried negative electrode slurry is calendered to form the negative electrode active layer.

12. The negative electrode manufacturing method according to claim 7, wherein... In the step of applying the magnetic field, the strength of the magnetic field is in the range of 1,000 to 10,000 G.

13. The negative electrode manufacturing method according to claim 7, wherein... After modifying the surface of the negative electrode current collector, the water contact angle of the negative electrode current collector is less than 50°.

14. The negative electrode manufacturing method according to claim 7, wherein... After modifying the surface of the negative electrode current collector, the water contact angle of the negative electrode current collector is 1° to 40°.

15. A lithium secondary battery, the lithium secondary battery comprising: Positive electrode; negative electrode; membrane; and electrolyte, among which The negative electrode is the negative electrode according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Milling method for agricultural products with increased content of indigestible starch

    KR1020250000909A